LITHIUM ION VS. LEAD ACID STARTER BATTERY OF MOTORCYCLE: TECHNICAL ASSESSMENT AND ECONOMIC FEASIBILITY MODEL - Teguh Juang Sinaga; Prof. Wahyudi Sutopo; Roni Zakaria Raung; Renny Rochani; Rina Wiji Astuti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Exposure to emissions from sealed lead-acid (SLA) starter batteries in internal combustion engine (ICE) motorcycles has been demonstrated to have serious impacts on human health and the environment. This has driven the transition to more environmentally friendly technologies. The objective of this study is to evaluate the technical feasibility, market share estimates, and economic viability of lithium starter batteries in Indonesia. The study employs System Dynamics and Probit analysis for the estimation of market potential and the economic feasibility. The findings indicate that LFP is technically more viable than NMC for replacing SLA in starter batteries applications. Investing in the LFP starter batteries business is economically viable. Price changes result in significant changes in the annual cash flow, IRR, NPV, and payback period. Furthermore, the model’s performance has been validated by experts and through statistical testing. Statistical test results showing a McFadden Pseudo R-squared score of 0.3049, indicating that the model’s performance is highly reliable. This study contributes to supporting businesses in the LFP starter batteries technology sector in commercializing their products, thereby helping to reduce lead emissions that are harmful to human health and the environment.